Analisis Regulasi Pengelolaan Limbah Fast Fashion di Indonesia: Implementasi Extended Producer Responsibility sebagai Instrumen Hukum dalam Pengelolaan Limbah Tekstil - Nasjwa Annisa Putri; Zahra Justicia Rahmah; Maret Priyanta (Student Research Journal, 2026)
The fast fashion industry has actually become the second largest contributor to textile waste in the world due to rapid production cycles, high consumer demand, and the use of synthetic materials that are difficult to biodegrade. This phenomenon causes serious environmental impacts such as water pollution, greenhouse gas emissions, accumulation of solid waste, and microplastic pollution that threatens marine ecosystems. In Indonesia, although environmental regulations such as Law Number 32 of 2009 concerning Environmental Protection and Management and Law Number 18 of 2008 concerning Waste Management exist, the implementation of fast fashion waste management still faces various obstacles. This study aims to analyze the implementation of waste management regulations in the fast fashion industry in Indonesia and to examine why the Extended Producer Responsibility (EPR) mechanism is necessary as a legal instrument for textile waste management. The method used is normative juridical with an ecological approach, utilizing primary and secondary legal materials, as well as qualitative-descriptive and comparative analysis with France, the Netherlands, and Sweden. The findings reveal four main legal gaps: the absence of a definition for post-consumer textile waste, the lack of a binding take-back mechanism for producers, weak fiscal instruments supporting EPR, and the absence of ecodesign obligations. The implication of this study highlights the need for regulatory reconstruction that specifically addresses the responsibility of fast fashion producers throughout the product life cycle to achieve more effective and sustainable waste management.